Teaching Teachers About Energy: Lessons from an Inquiry-Based Workshop for K-8 Teachers. - Tobin, Roger G.; Crissman, Sally.; Doubler, Sue.; Gallagher, Hugh M.; Goldstein, Gary.; Lacy, Sara.; Rogers, C.B.; Schwartz, Judah.; Wagoner, Paul. (Tufts University. Tisch Library., 2017)
We report results and impressions from a three-day inquiry-based workshop for K-8 teachers, aimed at improving their understanding of energy from a science and engineering perspective. Results suggest that the teachers made significant gains in understanding and appreciation of important energy concepts, but their comprehension of some key ideas remained incomplete. The dissipation of energy into thermal energy of the environment proved to be a particularly difficult idea, and one that represents a serious obstacle to understanding the principle of the conservation of energy.